PERFORMANCE AND LIFE CYCLE COST ANALYSIS OF A PHOTOVOLTAIC THERMOELECTRIC SYSTEM FOR ROOM COOLING APPLICATION - LOOI, KAR KIN (2019)
The integration of thermoelectric cooling system (TEC) into building application has attracted the attention of researchers in recent years due to the advantages of Freon-free. However, most of previous researches investigated the cooling performance of TEC under controlled environment and overlooked the factors such as the indoor relative humidity and thermal comfort. Therefore, this study is aimed to experimentally investigate the performance of a photovoltaic powered thermoelectric cooling system (PV-TEC) under tropical weather conditions, considering the indoor temperature, relative humidity, and thermal comfort in a test chamber of 3.6 m3 volume.